Answer: Choice A
x^2-12x+36; is a polynomial
===================================================
Step-by-step explanation:
Use the rule that (A-B)^2 = A^2 - 2AB + B^2 to show (x-6)^2 = x^2-12x+36 is an identity. In this case, A = x and B = 6
You could also use the FOIL rule or the distributive property as two alternatives.
The result is a polynomial because it consists of summing or subtracting various monomials. If we had terms that had say exponents of decimal numbers or negative values, then we wouldn't have a polynomial.